An Image of the Human Body and Its Relationship with Nature in the Statements of Supporters of Alternative Health Theories - Chudzik, Anna (Poznańskie Studia Slawistyczne, 2022)
The aim of the article is to present the image of the body in relation to nature appearing in statements of the supporters of alternative health theories, as well as the processes of mythization of nature. The research material consists of statements by members of discussion groups on Facebook, and the research methodology—tools of anthropological and cognitive linguistics. The first part of the article discusses the changes in the dominant paradigm of perception of the relationship between the body and nature, the second part contains a brief description of the research methods, and the third part is the analysis of the material.